Kasus Hipertensi pada Kehamilan di Indonesia - Novi Kartika Sari; Theodola Baning Rahayujati; Mohammad Hakimi (Berita Kedokteran Masyarakat (BKM), 2016)
Determinants of pregnancy hypertensive disorders in Indonesia PurposeThis study aimed to assess the determinant factors of gestational hypertension (HDP) in Indonesia.MethodsThis research was an observational analytic study using a cross-sectional design. Sampling was calculated using consecutive sampling technique. The subjects were all pregnant women aged 15-54 years old in 33 provinces in Indonesia and 9024 women were selected as subjects. Chi-square and binomial regression tests were used to analyze the determinants of HDP to see the value of the Ratio Prevalence (RP). ResultsThe prevalence of hypertension among pregnant women was 6.18% (558 people) after being adjusted with external variables which were potentially confounders. The highest of hypertension was found in West Java with 59 pregnant women (10.57%). Overweight and chronic hypertension were related to hypertensive disorders in pregnancy with RP: 2.13 (95% CI: 1.80-2.51); and in overweight with RP: 4.36 (95% CI: 3.6-5.26) in hypertension assessments. The use of contraceptives was not a risk factor for hypertensive disorders in Indonesia with RP 0.92 (95% CI: 0.76-1.10). ConclusionOverweight and chronic hypertension are risk factors for the incidence of hypertensive disorders in pregnancy in Indonesia.